2019
DOI: 10.7861/futurehosp.6-2-129
|View full text |Cite
|
Sign up to set email alerts
|

The Second Conversation project: ­Improving training in end of life care communication among junior doctors

Abstract: Second Conversation was felt to be of most value to newly qualified doctors and worked well on wards where length of stay was longer and EoLC conversations frequently happen. Further evaluation and exploration of patient and caregiver experiences is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It has been suggested that seniors underestimate the fear and apprehension felt by juniors having these conversations, so seniors do not consider routinely inviting juniors to observe them as a valuable learning tool. 2 The Second Conversation intervention promotes embedding supported learning within daily practice and encourages observation, direct experience and reflection. 2 The intervention was found to be effective on longerstay wards with frequent ACP; therefore, the authors acknowledge this may not be transferable to other environments.…”
Section: Education and Developing Clinical Practicementioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that seniors underestimate the fear and apprehension felt by juniors having these conversations, so seniors do not consider routinely inviting juniors to observe them as a valuable learning tool. 2 The Second Conversation intervention promotes embedding supported learning within daily practice and encourages observation, direct experience and reflection. 2 The intervention was found to be effective on longerstay wards with frequent ACP; therefore, the authors acknowledge this may not be transferable to other environments.…”
Section: Education and Developing Clinical Practicementioning
confidence: 99%
“…2 The Second Conversation intervention promotes embedding supported learning within daily practice and encourages observation, direct experience and reflection. 2 The intervention was found to be effective on longerstay wards with frequent ACP; therefore, the authors acknowledge this may not be transferable to other environments. Additionally, our study suggests the availability of both informal teaching and observational learning was highly dependent on specialty, which makes adopting a similar workplace-based intervention across the foundation programme problematic.…”
Section: Education and Developing Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…8 Models that integrate such training alongside daily clinical practice may be particularly promising. 9 Importantly, these should be supplemented with opportunities for emotional support and reflection to acknowledge and ameliorate the impact of the emotional labour these conversations can involve. 10…”
mentioning
confidence: 99%